IN SILICO DOCKING STUDIES OF PHYTOCOMPOUNDS ON PI3K/NF-ΚB MEDIATED SIGNALLING PATHWAY - P.A.NAZEEM,; LEKSHMYSREE S NAIR,; MEKHA MOHAN,; R.KESHAVACHANDRAN, (International Journal of Pharma and Bio Sciences, 2014)
Cancer cell invasion and metastasis are multistep processes influenced by the over expression of cell-secreted proteolytic enzymes such as Matrix metalloproteinases(MMPs).Phosphatidylinositide 3-kinase/Nuclear Factor of kappaB signaling pathways have been known to be involved in regulating MMP-9 expression. Synergistic targeting of these pathways using NF-κB and PI3K inhibitors may have great potential for cancer treatment. This paper focuses on identifying phytocompounds having anticancer potential to effectively inhibit PI3K and NF-κB. Thirty five phytocompounds with anticancer properties were utilized for the study. After screening out using Lipinski rule of five and ADMET, five compounds namely allixin, capsaicin, eugenol, niazimicin and piperine were docked with PI3K and NF-κB proteins. Niazimicin exhibited interaction for PI3K and NF-κB with residues CYS 633, ASP 632, GLN 392 and LYS 145 respectively. Niazimicin, a phytocompound of Moringa Oleifera which is an underexploited vegetable crop with medicinal properties showed maximum interaction with the targets.